Trauma-informed servant leadership in health and social care settings. Issue 3 (22nd July 2021) - Mahon, Daryl
Abstract : Purpose: Practitioners, organisations and policy makers in health and social care settings are increasingly recognising the need for trauma-informed approaches in organisational settings, with morbidity and financial burdens a growing concern over the past few years. Servant leadership has a unique focus on emotional healing, service to others as the first priority, in addition to the growth, well-being and personal and professional development of key stakeholders. This paper aims to discuss Trauma Informed Servant Leadership (TISL). Design/methodology/approach: A targeted review of the servant leadership and trauma-informed care literature was conducted. Relevant studies, including systematic review and meta-analysis, were sourced, with the resulting interpretation informing the conceptual model. Findings: Although there are general guidelines regarding how to go about instituting trauma-informed approaches, with calls for organisational leadership to adapt the often cited six trauma-informed principles, to date there has not been a leadership approach elucidated which takes as its starting point and core feature to be trauma informed. At the same time, there is a paucity of research elucidating trauma outcomes for service users or employees in the literature when a trauma-informed approach is used. However, there is a large body of evidence indicating that servant leadership has many of the outcomes at the employee level that trauma-informed approaches are attempting to attain. Thus, the author builds on a previous conceptual paper in which a model of servant leadership and servant leadership supervision are proposed to mitigate against compassion fatigue and secondary trauma in the health and social care sector. The author extends that research to this paper by recasting servant leadership as a trauma-informed model of leadership that naturally operationalises trauma-informed principles. Research limitations/implications: A lack of primary data limits the extent to which conclusions can be drawn on the effectiveness of this conceptual model. However, the model is based on robust research across the differential components used; therefore, it can act as a framework for future empirical research designs to be studies at the organisational level. Both the servant leadership and trauma-informed literatures have been extended with the addition of this model. Practical implications: TISL can complement the trauma-informed approach and may also be viable as an alternative to trauma-informed approaches. This paper offers guidelines to practitioners and organisations in health and social care on how to operationalise important trauma-informed principles through leadership. Social implications: This conceptual model may help reduce the burden of trauma and re-traumatisation encountered by practitioners and service users in health and social care settings, impacting on morbidity. Originality/value: To the best of the author's knowledge, this is a novel approach, the first of its kind.